Reducing the specific absorption rate (SAR) in human brain exposed to to mobile phone radiationu sing carbon nanotube (Sebha University Conference Proceedings, 2024)
The mobile phone emits electromagnetic energy at radio frequencies, and the amount of this energy that is absorbed by the human head is measured by the Specific Absorption Rate(SAR) , which must be within internationally permissible limits which are 1.6w/kg with an average of 1g of tissue, and 2w/kg with an average of 10 grams of tissue . This study suggests reducing the specific absorption rate (SAR) by using a shield material (carbon nanotubes(CNT)) with a thickness of (0.2cm) , Because of its electrical and magnetic properties , it has low conductivity and density. The (SAR) distribution was simulated in a 3D model of a human head exposed to the radiated field from a mobile phone formed by a Microstrip Patch antenna at a frequency of 1.8GHz . And using Maxwell's equations with appropriate boundary conditions to find the distributions of specific absorption rate in the brain. The maximum specific absorption rate in the brain was calculated at (2.47w/kg) without using the shield. And a value of (1.22w/kg) when using the shield material. The results of this shield were compared with some other shields and it was found that the CNT shield was the best in reducing SAR in the brain.